The relationship between social creativity and aggressive behavior among Chinese junior high school students: The moderating role of hostile attribution bias - Ren, Feifei; Sun, Yuanyuan; Ji, Lin; Wei, Xing (Frontiers in Psychology, 2022)
Recently, research has begun to pay attention to the dark side of creativity. This research attempted to explore the association between social creativity and aggressive behavior as well as the moderating role of hostile attribution bias. Data were obtained from 496 junior high school students in 2 cities in China using a convenience sampling technique. The results showed that different aspects of social creativity were different related to aggressive behavior. Specifically, appropriateness was negatively, and harmfulness was positively related to aggressive behavior; However, the relation between originality and aggressive behavior was not significant. In addition, hostile attribution bias moderated the relationships between appropriateness/harmfulness and aggressive behavior were. Specifically, the negative relation between appropriateness and aggressive behavior as well as the positive relation between harmfulness and aggressive behavior became non-significant when hostile attribution bias was low. Implications of this study are also discussed.